Special Half Lightlike Submanifolds of an Indefinite Cosymplectic Manifold - Dae Ho Jin (Journal of Function Spaces and Applications)
We study the geometry of half lightlike submanifolds 𝑀 of an indefinite cosymplectic manifold 𝑀. First, we construct two types of half lightlike submanifolds according to the form of the structure vector field of 𝑀, named by tangential and ascreen half lightlike submanifolds. Next, we characterize the lightlike geometries of such two types of half lightlike submanifolds.